Study on Emission Reduction Strategies of Dual-Channel Supply Chain Considering Green Finance - Che, Cheng; Chen, Yi; Zhang, Xiaoguang; Zhao, Liangyan; Guo, Peng; Ye, Jingwen (Frontiers in Environmental Science, 2021)
As a weapon for economic development, green finance plays an important supporting and promoting role in the economic recovery and transformation of enterprises in the post-epidemic era. By constructing a dual-channel supply chain model, this paper considers two situations in which manufacturers participate in carbon trading and green finance loans, and uses Stackelberg game to study the impact of different situations on participants' profits and emission reduction decisions.The results show that: under the carbon trading mechanism, the carbon emission reduction level of the manufacturer is inversely proportional to the relevant price, and the demand and profit of the two channels increase with the increase in emission reduction; when carbon trading and green financial loans are carried out at the same time, participants have lower profits, but with the increase in emission reductions, it is still a growing trend.